Investigating the role and regulation of GPNMB in progranulin-deficient macrophages - Gillett, Drew A.; Neighbarger, Noelle K.; Cole, Cassandra; Wallings, Rebecca L.; Tansey, Malú Gámez (Frontiers in Immunology, 2024)
Progranulin (PGRN) is a holoprotein that is internalized and taken to the lysosome where it is processed to individual granulins (GRNs). PGRN is critical for successful aging, and insufficient levels of PGRN are associated with increased risk for developing neurodegenerative diseases like AD, PD, and FTD. A unifying feature among these diseases is dysregulation of peripheral immune cell populations. However, considerable gaps exist in our understanding of the function(s) of PGRN/GRNs in immune cells and their role in regulating central-peripheral neuroimmune crosstalk. One of the most upregulated genes and proteins in humans with GRN haploinsufficiency and in aged Grn knock-out (KO) mice is glycoprotein non-metastatic B (GPNMB) but its normal role within the context of immune crosstalk has not been elucidated. We addressed this gap by investigating the regulation of GPNMB in peritoneal macrophages of young WT or Grn KO mice, and discovered that GPNMB is actively increased as a result of insufficient progranulin at a very early age relative to previous reports. Mechanistically, the GPNMB extracellular domain (GPNMB ECD) is shed to negatively regulate inflammatory responses in macrophages and re-addition of PGRN rescues the phenotype. We also found that Microphthalmia-associated Transcription Factor (MITF) is also dysregulated in Grn KO macrophages; however, its nuclear translocation and activity are not required to rescue the immune dysregulation of Grn KO macrophages, suggesting redundancy in the system. These findings highlight the fact that knowledge of early-stage disease mechanism(s) in peripheral populations may inform treatment strategies to delay disease progression at an early, prodromal timepoint prior to development of neuroinflammation and CNS pathology.